Navigating ethical challenges in second language narrative inquiry research. (November 2021) - De Costa, Peter I.; Randez, Robert A.; Her, Lee; Green-Eneix, Curtis A.
Abstract: Methodological and theoretical innovations in second language (L2) narrative research have yielded helpful insights into L2 learning and teaching over the past four decades. However, with the creation of this vibrant line of inquiry, new ethical dilemmas have correspondingly emerged. These dilemmas threaten to violate the core ethical principles of (1) respect for persons, (2) yielding optimal benefits while minimizing harm, and (3) the preservation of justice. Building on recent ethics-inflected applied linguistics work that has distinguished between macroethics (procedural ethics of review boards and professional codes of conduct) and microethics (everyday ethical dilemmas encountered in specific research contexts), we explore how ethical challenges have been negotiated by L2 narrative researchers. The article closes with suggested ethical measures that need to be taken in the future as researchers continue to refashion narrative inquiry to meet evolving intellectual demands.